Trends and Risks in Mergers and Acquisitions: A Review - Manuel García-Nieto; Vicente Bueno-Rodríguez; Juan Manuel Ramón-Jerónimo; Raquel Flórez-López (Risks, 2024)
This study examines risk factors in mergers and acquisitions (M&As) identified in the recent literature, addressing the following question: “What risk factors associated with M&A transactions are discussed in the recent academic literature?” A semi-systematic literature review was conducted using a comprehensive search strategy with targeted keywords related to M&A risks. Papers from 2020 to 2024 were selected based on quality and relevance, with detailed review of abstracts and titles. Co-occurrence analysis using VOSviewer software (version 1.6.20) was applied to categorize key themes. The review of 118 papers identified four main risk categories: information asymmetry; performance and corporate reputation; litigation and investor protection; and geopolitical factors. Findings reveal complex interdependencies among these risks, highlighting the need for a holistic approach to risk management. Corporate social responsibility (CSR) is crucial for mitigating risks, improving transparency, and enhancing reputation. This study offers recommendations for better financial disclosures, robust environmental, social and governance strategies, and the integration of digital finance technologies as blockchain in M&A activity. Future research should include longitudinal studies on M&A risk dynamics, case studies on corporate governance, advanced valuation methods, and comparative analyses across regions and industries, focusing on emerging technologies like AI and blockchain.